A REVISION OF THE GENUS TOLUMNIA STAL (PENTATOMIDAE: PENTATOMINAE: CARPOCORINI) FROM THE INDO-PAKISTAN SUB-CONTINENT (Biological Sciences - PJSIR, 2022)
The genus Tolumnia Sti'llfrom the Indo-Pakistan subcontinent is revised. Five species are keyed and described withspecial reference to their metathoracic scent gland complex, male and female genitalia and their relationships within thetribe Carpocorini Slill is also briefly discussed.